Adverse Events of Antiepileptic Drugs Using Indonesian Version of Liverpool Adverse Events Profile - Astri Budikayanti; Lubna Muhammad Qadri; Zakiah Syeban; Luh Ari Indrawati; Fitri Octaviana (Neurology Research International)
Introduction. Adverse events (AEs) associated with antiepileptic drugs (AEDs) affect people with epilepsy’s (PWE) quality of life. A study conducted in 15 European countries showed that the AEs prevalence of AEDs in PWE was up to 80%. To date, there are no validated screening instruments to detect AEs of AEDs in Indonesian PWE. Therefore its epidemiology is currently unknown. This study aimed to validate the Indonesian version of Liverpool Adverse Events Profile (LAEP), consequently increasing physicians’ awareness toward the probability of AEs and its necessary evaluation. Furthermore, this study was intended to determine the AEs prevalence of AEDs in Indonesian PWE. Methods. The questionnaire was translated from English into Indonesian version. The validity and reliability were tested using Spearman correlation and Cronbach’s alpha measurement. An observational cross-sectional study was carried out on consecutive PWE in outpatient clinic, Cipto Mangunkusumo Hospital. We analyzed duration of epilepsy, onset of epilepsy, seizure frequency, type of epilepsy, etiology and epilepsy syndrome, number of AEDs, duration of AED use, and comorbidity. Results. All of the 19 items in the questionnaire were valid, with correlation coefficient ranging from 0.465 to 0.690 (moderate-strong correlation). Cronbach’s alpha value was 0.846 (good consistency). The total of 90 subjects were enrolled with 91% screened as having AEs using LAEP questionnaire. The most common AEs were tiredness (67.8%), sleepiness (66.7%), memory problems (62.2%), and difficulty in concentrating (56.7%). The only clinical variable that influenced AEs was polytherapy. Conclusion. The Indonesian version of LAEP was a valid and reliable instrument to screen AE of AEDs in PWE. Almost all the subjects in this study were suspected having AEs. Polytherapy was the independent factor of AE.